An objectivist-constructivist blended approach: implications on student achievement and satisfaction in Malaysian university-level beginner string technique classes / Shafizan Sabri - Sabri, Shafizan (Institute of Graduate Studies, UiTM, 2016)
This study explores the impact of blended-approach teaching on students’ achievement and satisfaction in a Malaysian university-level beginner string classes. Specifically, this study incorporated a blended objectivist– constructionist approach, together with Dick and Carey’s (Dick, Carey and Carey, 2005) instructional design system, to create instructional materials for beginner string technique class. Researchers in general concur that the objectivist and constructivist approaches positively affect the teaching and learning process in the music classroom. Specifically, the constructivist teaching strategy of modeling, communication, exploration, and experimentation has been proven effectual in enhancing students’ achievement and potential. Hence, these teaching strategies were incorporated into the blended approach to put together innovative instructional materials for teaching beginner string ensembles. This research used a non-equivalent control group post-test under a quasi-experimental design. The sample of the study consisted of 40 music students from two public universities in Malaysia. None of the students had had any prior instrumental music training. The students were purposively allocated to one of the two instructional material; these were (a) an experimental group that were subject to the blended approach, using instructional materials based on Dick and Carey (Dick, Carey and Carey, 2005) ;and (b) a control group that received conventional teaching via instructional materials based on printed method books. Following the 14-week treatment, the students completed an achievement test, performance assessment, and satisfaction survey…